Persistensi dan Variabilitas Hidrometeorologi Daerah Aliran Sungai Citarum - Ruminta Ruminta; Bayong Tjasyono Hanggoro K.; Indratmo Soekarno (Institut Teknologi Bandung, 2006)
The persistences and variabilities of the hydrometeorology had been studied in the Upper Citarum River Basin, West Java, based on monthly observations data of the rainfall, evapotranspiration, humidity, and runoff from January 1968 to December 2000 and monthly global phenomena data from National Centers for Environmental Prediction (NCEP) and National Centers for Atmospheric Research (NCAR) reanalyses. The results showed that rainfall, evapotranspiration, and humidity have two firm persistences i.e. wet and dry periods, while the runoff has no firm persistence. The stability of rainfall and humidity were less than evapotranspiration and runoff; the stability patterns of rainfall tend to increase, whereas, the evapotranspiration tend to decrease; the stability patterns of the humidity and runoff have no firm trends; the rainfall and runoff have very high variability i.e., 73% and 62%, respectively. The result indicated that the processes of the rainfall and runoff were very chaotic, while evapotranspiration and humidity have low variability i.e., 19% and 3%, respectively. These data indicated that the evapotranspiration and humidity have low pattern, variability patterns of the all hydrometeorological components had increasing trends, the hydrometeorological components were influenced by global phenomena as a consequence of the significant correlations between hydrometeorological components and some global phenomenas, especially Central Indian Precipitation (CIP), Global Temperature (GT), Dipole Mode Index (DMI), Pacific Warm Pool (PWP), and Precipitable Water (PW).